1971
DOI: 10.1111/j.1365-2621.1971.tb06380.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Composition and Stability of Sausage‐type Emulsions

Abstract: A laboratory technique for the preparation of small batches of sausage emulsion was developed for a comparative study of the effectiveness of fresh and frozen beef in achieving emulsion stability.The technique consisted of three basic steps: (I) low speed chopping and blending of ingredients at -2" to +20c; (2) low speed blending with the gradual addition of soybean oil at 2" -8°C; and (3) high speed chopping to a temperature of 15"16°C.The preparation and evaluation of emulsions with widely varying compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Hence, fat level had only a small, nonsystematic effect on WBA. These results agree with earlier work (Morrison et al, 1971) which found that a constant effective salt concentration of 3.0%, reducing the fat concentration from 60 to 20% produced only a small decrease in WBA.…”
Section: Effect Of Fat Level On Wbasupporting
confidence: 95%
“…Hence, fat level had only a small, nonsystematic effect on WBA. These results agree with earlier work (Morrison et al, 1971) which found that a constant effective salt concentration of 3.0%, reducing the fat concentration from 60 to 20% produced only a small decrease in WBA.…”
Section: Effect Of Fat Level On Wbasupporting
confidence: 95%
“…The data are consistent with results of MORRISON et al [12]. They have found the relationship between cooking stability and physical properties of sausage-type emulsions prepared from frozen beef muscles stored at -27 "C up to 27 days.…”
supporting
confidence: 92%
“…To determine the emulsion stability, the weights of the sausages were measured, before and after the cooking process, and multiplied by 100. In addition, the exuded juice from the vacuum-packed sausages was weighed and its percentage was calculated taking into account the initial weight of the packed sausage multiplied by 100% (Morrison, Webb, Blumer, Ivey, & Haq, 1971).…”
Section: Physical Analysismentioning
confidence: 99%